Knowing human movement - Estes, Steven (Allyn and Bacon, 1999)
Introdution, Terms and Definitions about Human Movement. Knowing it through Authority, Thought, Observation, Experimentation, Awareness, and Story telling. The Nature of Human movement. An Overview of the Development and Reform of Modern Physical Education and Sport.